2015
DOI: 10.1109/jbhi.2015.2479625
|View full text |Cite
|
Sign up to set email alerts
|

Dual Motor-Cognitive Virtual Reality Training Impacts Dual-Task Performance in Freezing of Gait

Abstract: Freezing of gait (FOG), an episodic gait disturbance characterized by the inability to generate effective stepping, occurs in more than half of Parkinson's disease patients. It is associated with both executive dysfunction and attention and becomes most evident during dual tasking (performing two tasks simultaneously). This study examined the effect of dual motor-cognitive virtual reality training on dual-task performance in FOG. Twenty community dwelling participants with Parkinson's disease (13 with FOG, 7 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 38 publications
0
51
1
1
Order By: Relevance
“…9,10 Previous studies have observed that reduced gait initiation time and lower-body symptoms may be related to physiological alterations in both motor and cognitive systems. [11][12][13] A recent study completed in more than one hundred PD patients proposed that gait, rather than cognition, predicts decline in cognitive domains early in PD, 14 suggesting gait might be a clinical biomarker for PD cognitive decline in early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Previous studies have observed that reduced gait initiation time and lower-body symptoms may be related to physiological alterations in both motor and cognitive systems. [11][12][13] A recent study completed in more than one hundred PD patients proposed that gait, rather than cognition, predicts decline in cognitive domains early in PD, 14 suggesting gait might be a clinical biomarker for PD cognitive decline in early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, successful locomotion requires the ability of performing simultaneously a cognitive task that can cause an interference in gait performance, especially in older adults. Several works showed the efficacy of this paradigm [ 17 , 18 , 19 , 20 ]. The age-related decrease in attentional and executive functioning would impair the ability of managing the concurrent execution of different motor and cognitive activities, normally occurring in everyday life [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paroxysmal symptom affects over half of people with Parkinson's disease (PD) over time (Giladi and Nieuwboer, 2008) and is closely associated with falls and admissions to nursing homes (Bloem et al, 2004). The pathophysiology of FOG remains poorly understood but freezing is closely associated with deficits in motor parameters, such as stride time, gait symmetry and rhythmicity (Killane et al, 2015) and cognitive impairment, especially, executive dysfunction (Maruyama andYanagisawa, 2006, Amboni et al, 2008). Executive function is impaired in PD with FOG (FOG+) compared to those without FOG (FOG-).…”
Section: Introductionmentioning
confidence: 99%